Novel HIVEP1-ALK fusion in a patient with lung adenocarcinoma demonstrating sensitivity to alectinib: a case report - Gu, Xiaodong; Wang, Wenxian; Wu, Wei; Zhang, Yiping; Shao, Lan; Santarpia, Mariacarmela; Christopoulos, Petros; Myall, Nathaniel J.; Shi, Zhiyong; Lou, Guangyuan (Translational Lung Cancer Research, 2022)
Novel HIVEP1-ALK fusion in a patient with lung adenocarcinoma demonstrating sensitivity to alectinib: a case report
Gesehen am 06.09.2022